Health Systems Engineering Fellowship: Curriculum and Program Development. (March 2015) - Watts, Bradley V.; Shiner, Brian; Cully, Jeffrey A.; Gilman, Stuart C.; Benneyan, James C.; Eisenhauer, William
Industrial engineering and related disciplines have been used widely in improvement efforts in many industries. These approaches have been less commonly attempted in health care. One factor limiting application is the limited workforce resulting from a lack of specific education and professional development in health systems engineering (HSE). The authors describe the development of an HSE fellowship within the United States Department of Veterans Affairs, Veterans Health Administration (VA). This fellowship includes a novel curriculum based on specifically established competencies for HSE. A 1-year HSE curriculum was developed and delivered to fellows at several VA engineering resource centers over several years. On graduation, a majority of the fellows accepted positions in the health care field. Challenges faced in developing the fellowship are discussed. Advanced educational opportunities in applied HSE have the potential to develop the workforce capacity needed to improve the quality of health care.